(untitled) (مجلة ديالى للبحوث الانسانية, 2022)
This study was conducted in 10 dsm-1 salt effected soil in Kharif 2004. The treatments tested were T1, T2, T3, T4 and T5 equivalent to 0.0, 0.25, 0.5, 0.75, and 1 ml of H2SO4 / Kg of soil respectively. Two varieties of wheat were grows Abu-Graib and Ibaa -99. Morphological and physiological parameters (plant height, leaf area, Straw and seed weight) were studied. In Abu-Graib variety the result shows significant increase in all parameters in T3, T4, and T5 is compared with control and high increased obtained in T5. While in Ibaa variety significant increase obtained in T4 and T5 only and high increased obtained in T4 comparative with control